2008
DOI: 10.4028/www.scientific.net/msf.604-605.239
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Properties of Steels with Ultrasonic Attrition Treated Surface Layers

Abstract: Severely deformed surface layers have been created by ultrasonic attrition technique on four steel sheets to investigate their influence on fatigue behaviour. A low-carbon (0.05%) ferritic steel and a medium-carbon (0.47%) normalized ferritic-pearlitic steel were selected to study the effect of carbon content on fatigue properties of carbon steels. Two stainless steels, Type 316L and Type 301LN, were also tested to study the influence of stability of the austenitic structure. Microstructural features were char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…Therefore, the formation of those ultrafine-grains should be due to microstructural changes introduced by the high local plastic deformation. This agrees with the results by Uusitalo et al [37] and Thiriet et al…”
Section: Figure 4 A) Cross-section Electron Backscattered Diffractiosupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, the formation of those ultrafine-grains should be due to microstructural changes introduced by the high local plastic deformation. This agrees with the results by Uusitalo et al [37] and Thiriet et al…”
Section: Figure 4 A) Cross-section Electron Backscattered Diffractiosupporting
confidence: 94%
“…Uusitalo et al [37] reported an ultrafine-grain layer of a thickness around 10 m for both a stable austenitic steel (AISI 316L) and the same metastable grade used in the present work, i.e., AISI 301LN. A similar layer, although of higher thickness (75 m), was measured by Thiriet et al [38] on AISI 316L.…”
Section: Figure 4 A) Cross-section Electron Backscattered Diffractiomentioning
confidence: 56%
“…From the data, it can be seen that the stress amplitude, which does not result in failure in 2 × 10 6 cycles, termed as fatigue stress limit (FL) here, has been determined as 400 MPa for all TWIP steels. For comparisons, the S-N curves of two commercial austenitic stainless steels, Types 301LN and 316L, are also inserted, obtained in similar fatigue testing, showing FL of about 350 and 300 MPa, respectively [19]. For Types 304 and 316 stainless steels, FL of 240 and 270 MPa, respectively, have been reported in reverse Table 2 Quasi-static tensile properties (the yield strength, tensile strength and total elongation) of the TWIP steels and three austenitic stainless steels [18].…”
Section: Initial Microstructures and Mechanical Propertiesmentioning
confidence: 99%
“…Bending stress vs cycles to failure curves of the investigated TWIP steels and those of 301LN, 316L, and high-strength TRIP steels used for comparison [13,14]. Relationship between the FL and tensile strength of steels fromFig.…”
mentioning
confidence: 99%